نظام تلقائي لتسجيل الحضور باستخدام التعرف على الوجوه - بقاص اكرام , قده نور ,كحلة شيراز (university of eloued جامعة الوادي, 2024)
تقنية التعرف على الوجه هي تقنية تحدد أو تتحقق من هوية الشخص من خالل تحليل ومقارنة األنماط في مالمح الوجه. تتضمن هذه التقنية اكتشاف واستخراج معالم الوجه. يهدف التقرير الحالي إلى بناء نظام حضور تلقائي باستخدام تقنية التعرف على الوجه باستعمال خوارزميات التعلم العميق، التي تحسن بشكل كبير دقة وكفاءة أنظمة التعرف على الوجه مقارنة بالطرق غير المعتمدة على التعلم العميق Face recognition is a technology that identifies or verifies a person’s identity by analyzing and comparing patterns in facial features. It involves detecting and extracting facial landmarks. The objective of the current report is to build an automatic attendance system using face recognition with deep learning algorithms, which significantly improve the accuracy and efficiency of face recognition systems compared to non-deep learning methods.
مدكرة ليسانس اعلام الي
Keywords: نظام الحضور االوتوماتيكي ، التعرف على الوجه، التعلم العميق.; Automatic attendance system; Face recognition; Deep learning.